2017
DOI: 10.1186/s40659-017-0138-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical and behavioral characterization of neuronal glutamate transporter EAAT3 heterozygous mice

Abstract: BackgroundObsessive–compulsive disorder (OCD) is a severe neuropsychiatric condition affecting 1–3% of the worldwide population. OCD has a strong genetic component, and the SLC1A1 gene that encodes neuronal glutamate transporter EAAT3 is a strong candidate for this disorder. To evaluate the impact of reduced EAAT3 expression in vivo, we studied male EAAT3 heterozygous and wild-type littermate mice using a battery of behavioral paradigms relevant to anxiety (open field test, elevated plus maze) and compulsivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Our results are in agreement with this hypothesis, by showing that EAAT3 glo /CMKII mice display increased behaviors that are relevant to OCD. Of note, several reports using different mouse models fully or partially lacking EAAT3 have shown unaltered baseline anxiety-like or repetitive behaviors, indirectly supporting the potential involvement of EAAT3 gain-of-function in behaviors relevant to OCD [39,40,60] (however, see [61]).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our results are in agreement with this hypothesis, by showing that EAAT3 glo /CMKII mice display increased behaviors that are relevant to OCD. Of note, several reports using different mouse models fully or partially lacking EAAT3 have shown unaltered baseline anxiety-like or repetitive behaviors, indirectly supporting the potential involvement of EAAT3 gain-of-function in behaviors relevant to OCD [39,40,60] (however, see [61]).…”
Section: Discussionmentioning
confidence: 94%
“…Several animal models fully or partially lacking EAAT3 have shown no alterations in baseline behaviors relevant to OCD [39,40,41]. Interestingly, the rs301430C allele, a SLC1A1 polymorphism highly replicated in OCD studies is associated with increased transcript levels in human brain tissue [27], suggesting that overexpression could contribute to OCD susceptibility [4].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, behavioral profiling of the Slc1a1 null and STOP mice has primarily focused on comparing homozygous mutant animals with either wildtype littermate controls or age-and sex-matched controls, without extensive characterization of heterozygous animals demonstrating 50% loss of expression. Two groups have recently reported behavioral profiling of animals heterozygous for Slc1a1 and found no change in locomotor activity but reported different results regarding anxiety-like behavior compared to wildtype littermate controls (Afshari et al, 2015;Gonzalez et al, 2017). Heterozygotes also had no response to amphetamine and no change in tissue dopamine levels (Gonzalez et al, 2017).…”
Section: Eaat3 In Development and Adulthoodmentioning
confidence: 99%
“…Two groups have recently reported behavioral profiling of animals heterozygous for Slc1a1 and found no change in locomotor activity but reported different results regarding anxiety-like behavior compared to wildtype littermate controls (Afshari et al, 2015;Gonzalez et al, 2017). Heterozygotes also had no response to amphetamine and no change in tissue dopamine levels (Gonzalez et al, 2017). Overall, the behavioral data across these different studies is not directly comparable because of the use of different mechanisms (null versus STOP versus heterozygote), ages (from weanlings to adults), and controls (littermates versus matched wildtypes).…”
Section: Eaat3 In Development and Adulthoodmentioning
confidence: 99%
“…Mouse models lacking EAAT3 expression have reported dissimilar results in regard to OCD-like behavior. EAAT3 heterozygous mice were found to have no behavioral or neurochemical alterations relevant to OCD ( González et al, 2017 ). In EAAT3 knockout (KO) mice, early studies found no alterations in anxiety or compulsive-like behaviors at 6–8 weeks old but reported a reduction in self-grooming behavior at 10–12 months old ( Aoyama et al, 2006 ), while a recent study found increased grooming in EAAT3 KO mice at an early age, from postnatal day 14 to 35 ( Bellini et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%